Determinants of virological failure among patients on first line highly active antiretroviral therapy (HAART) in Southwest Ethiopia: A case-control study - Biruk Bogale; Adane Asefa; Alemnew Destaw; Gachana Midaksa; Zufan Asaye; Mathewos Alemu Gebremichael; Asrat Arja Wolde; Ejig Yimer; Tewodros Yosef (Frontiers Media S.A., 2022)
BackgroundVirological failure remains a public health concern among patients with human immunodeficiency virus (HIV) after treatment initiation. Ethiopia is one of the countries that aims to achieve the global target of 90-90-90 that aims to achieve 90% virological suppression, but there is a paucity of evidence on the determinants of virological failure. Therefore, the study is intended to assess determinants of virological treatment failure among patients on first-line highly active antiretroviral therapy (HAART) at Mizan Tepi University Teaching Hospital (MTUTH), Southwest Ethiopia.MethodA hospital-based unmatched case-control study was conducted from 11 November to 23 December 2020, among 146 cases and 146 controls. All cases and controls were selected randomly using computer-generated random numbers based on their medical record numbers. During the document review, data were collected using checklists, entered into Epi-data version 4.0.2, and analyzed by SPSS version 25. A multivariable logistic regression analysis was done to identify the independent determinants of virological treatment failure.ResultsIn this study, being male (adjusted odds ratio (AOR) = 1.89, 95% CI: 1.04, 3.47), substance use (AOR = 2.67, 95% CI: 1.40, 4.95), baseline hemoglobin (Hgb) < 12 mg/dl (AOR = 3.22, 95% CI: 1.82, 5.99), poor drug adherence (AOR = 3.84, 95% CI: 1.77, 5.95), restart ART medication (AOR = 2.45, 95% CI: 1.69, 7.35), and opportunistic infection (OI) while on HAART (AOR = 4.73, 95% CI: 1.76, 12.11) were determinants of virological treatment failure.ConclusionThe study revealed that the sex of the patient, history of substance use, baseline Hgb < 12 mg/dl, poor drug adherence, restart after an interruption, and having OI through the follow-up period were determinants of virological failure. Therefore, program implementation should consider gender disparity while men are more prone to virological failure. It is also imperative to implement targeted interventions to improve drug adherence and interruption problems in follow-up care. Moreover, patients with opportunistic infections and restart HAART need special care and attention.